Vegetal structure and diversity in a pine-oak forest with disturbances in different chronosequences - Ruiz González, Miguel Ángel; Campos Angeles, Gisela Virginia; Reyes Hernández, Valentín José; Rodríguez Ortiz, Gerardo; Enríquez del Valle, José Raymundo (Instituto de Ecología, A.C., 2022)
The dynamics that the structure and diversity of the vegetation follow in a site after suffering a disturbance is an indicator of the resilience of the affected ecosystem. Therefore, the floristic composition and changes in plant succession were analyzed according to the chronosequence of different disturbances, in a pine-oak forest in southern Oaxaca, Mexico. Selective sampling was used, 28 sampling sites of 400 m2 were established, in which a census of all vascular individuals was carried out during the dry and rainy seasons of 2018. Alpha and beta diversity were estimated and analyzed; the vertical and horizontal structure in all the chronosequences: 1) fires, (IF), occurred one (IF-1), five (IF-5) and six (IF-6) years ago; 2) farmland with agricultural fallow, (DA), eight (DA-8) and 20 years (DA-20); 3) free grazing (PA) and, 4) a reference area, without intervention (C1). The highest richness (89) was recorded during the rainy season (F = 0.0154) in an area with agricultural fallow for 20 years. In the area burned a year earlier, the lowest diversity Shannon=1.26 and Shannon=1.60 was observed in both seasons. The highest importance value index (86.55%) was calculated for Pinus lawsonii Roezl in the area burned six years ago. The disturbance caused by fire is the one that caused the greatest damage to the structure and diversity of the vegetation, but it was also the one in which the vegetation appeared in less time after it. The floristic composition varied according to the type, severity and time elapsed after the disturbance, while the richness of species was related to the plant structure in the site, which determines the microenvironmental conditions. The results are useful for implementing restoration and conservation measures.